Morfometria, qualidade do tronco e da copa de Peltophorum dubium (Spreng.)Taub. em povoamento experimental no estado do Rio Grande do Sul - Silva, Lorenzo Teixeira de Melo da (2007)
With the necessity of knowledge of the growth of canafistula, Peltophorum dubium (Spreng.) Taub., in homogeneous stands, in the adult age (24 years), it was analyzed a bifactorial experiment with initial spacing of the plants (2 m x 2 m, 2 m x 3 m, 2 m x 4 m) and seedling types (nude root and packaged root) using blocks at random. It was quantified qualitative variables as stem rectitude, crow symmetry and the stem length with morphometric variables as the diameter at the breast height (d), total height (h), number of trees per hectare (N), Assmann dominate height (h100), basal area per hectare (G) and the hypsometric relation for the species (h/d). The qualitative data was analyzed using the Chi-Square test by contingency tables, testing the dependency and the homogeneity among the qualitative variables and tree diameters. The morphometric variables were analyzed by variance and covariance analyzes using the factors: seedling, spacing, blocks, number of trees per hectare and dominate high class. The results shown that: the use of mathematical model in a bifactorial experiment using the random blocks delineation, with spacing and seedling factors, after 24 years show limitations in the analyze because of the surviving differences. The use of the number of tress per hectare and dominate high class as explicative factors to the morphometric variables show good estimatives for the stand. The medium diameter, as the basal area per hectare, were significantly influenced by the density variations and dominate high class, showing different medians only for extreme densities of 1250 and 2500 trees per hectare. For the h100, the medium diameter and G were significantly different in all the classes, showing bigger diameters in the class of 1250 trees per hectare and bigger G in the class of 2500 trees for hectare. The median height and the stem height showed similar behavior to the analyzed factors, being significantly affected only for the h100 classes. As bigger the h100 class as bigger is the median height and the steam height. The hypsometric relation for canafistula was significantly influenced by classes of number of trees per hectare and dominate high classes, showing differences of inclination only for dominate high classes, in which the curves more accentuated are found in the superior classes of dominant height. The classes of number of trees per hectare determine only variation of levels to hypsometric relation, such that how much bigger the densities lesser were the levels to the hypsometric relation, granting by the statistic just in the minor classes of dominant height. Qualitative variables of canafistula, as stem rectitude and stem length showing that there were dependence by Chi-Square test, but with weak association, being that crow symmetry showing bigger ratios for long and straight steams. And how much bigger the diametric, bigger are the ratios of pantries symmetrical, straight and long steams.